PENERAPAN THINK, TALK, AND WRITE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR IPS SISWA KELAS VIII SMP KRISTEN SATYA WACANA SALATIGA - Endy Liani Klarita; Arief Sadjiarto (Satya Widya, 2019)
This research was conducted with problems in class VIII students, amounting to 20 students at the Satya Wacana Christian Middle School in Salatiga regarding critical thinking skills and learning outcomes. Therefore researchers want to take action to improve learning by using the Think Talk and Write (TTW) model. This type of research is the study of class action using Kurt Lewin's research design. The instrument of data collection uses test instruments, observation sheets, and questionnaires. Analysis of the data used is descriptive comparative. The indicator of the success of critical thinking skills and learning outcomes is 75%. The results obtained from this study are that there is an increase in critical thinking skills and learning outcomes of class VIII Satya Wacana Christian Middle School Salatiga. In the first cycle the results of critical thinking skills are 55% of students who have high critical thinking skills, while in the second cycle there is an increase of 85% of students who have high critical thinking skills. Then in the pre-cycle learning outcomes there were 25% of students whose grades reached KKM, the first cycle there were 70% of students completed KKM, and in the second cycle there was an increase of 90% of students who completed KKM. So the conclusion in this study that the use of Think Talk and Write (TTW) learning model can improve critical thinking skills and student learning outcomes in social studies subjects of class VIII Satya Wacana Christian Middle School Salatiga.